Prenatal care: a look at the quality - Mayenne Myrcea Quintino Pereira Valente; Naiana Queiroz de Freitas; Aline Cruz Esmeraldo Áfio; Carla Suellen Pires de Sousa; Danielle Rosa Evangelista; Escolástica Rejane Ferreira Moura (Rev Rene)
This study aimed to assess the quality of prenatal care according to the criteria established in the Prenatal and Birth Humanization Program. Cross-sectional, descriptive and exploratory study carried out with 75 pregnant women registered in Basic Health Units of a municipality in the metropolitan region of Fortaleza, Ceará, Brazil. Data were collected between March and May, 2011, through interviews during prenatal nursing consultations. One highlighted major obstacles to a good quality prenatal care: deficits in the request of second routine laboratory tests in prenatal care, significant number of pregnant women who were not tested for fetal presentation and a small number of pregnant women who did not have the updated vaccine schedule. However investment is necessary to encourage and qualify professionals to perform their practices with a better performance. These practices can be developed through educational and health actions in order to improve the quality of prenatal care.